Outdoor Learning Methods to Improve Students' Biological Concepts - Akmalsyah Akmalsyah (Journal of Biological Science and Education, 2020)
Outdoor learning is a method in learning and teaching. With outdoor learning, students can get to know the environment and biological concepts. The purpose of this study was to determine the increase in students' understanding of the concept of the interaction between living things and the environment in the outdoor learning method. This type of research is a classroom action research (CAR) with two learning cycles. The subjects of this study were students of class X SMPN 15 Kabaena Utara with 20 students. The data obtained were analyzed using descriptive analysis. The results showed that the students' understanding of the concept of cycle 1 was 40.95 and cycle 2 was 70.5. Based on the results of the study, it can be concluded that the outdoor learning method can improve the understanding of biological concepts in class X SMPN 15 Kabaena Utara.Keywords: Outdoor Learning Method, Biological Concept Students